SIFAT MEKANIKA KAYU PINUS (Pinus merkusii Jungh et de Vriese) ASAL DESA TAENDE MORI ATAS MOROWALI UTARA SULAWESI TENGAH - Lapeantu, Smith Krisno; Hapid, Abdul; Muthmainnah, Muthmainnah (Universitas Tadulako, 2017)
The mechanical characteristic of wood also known as the strength of wood, the characeristic that related to the wood endurance in holding load and content that given to it. The research aimed to find out the wood mechanical characteristic that involved parallel press strength of fiber, static curve strength (MOE) and broken strength (MOR) of pine (Pinus merkusii Jungh et de Vriese) wood from Taende village Upper Mori subdistrict Morowali Utara District Central Sulawesi. The observed Variabel of the research was the mechanical characteristic of Pine wood that involved the parallel press strength of fiber, the static curve strength (MOE) and the broken strength (MOR). The experiment design that used in the research was Complete Ramdomized Design (CRD) with three treatments of posititions in the stem: base, middle and tip. Each treatment was repeated six times, so there would be 36 units of experiment samples. The result of the research showed that the rate of the parallel press strength and the highest rate of the base was 453,61 kg/cm2, the middle was 324,50 kg/cm2 and the lowest rate of the tie was 269,53 kg/cm2. The highest rate of the static curve strength (MOE) on the base was 62.400,19 kg/cm², the middle was 60.716,01 kg/cm² and the lowest rate on the tip was 59.479,52 kg/cm². The higjest rate of the broken strength (MOR) on the base was 464,80 kg/cm², the middle was 427,81 kg/cm² and the lowest rate on the tip was 386,28 kg/cm². Statistically, the position in the stem had unreal effect to the parallel press strength of fiber MOE and the broken strength MOR of the pine wood was axial one direction.Keywords: Characteristic, Pine wood mechanical, Pinus merkusii